Basic psychological need satisfaction of collegiate athletes: the unique and interactive effects of team identification and LMX quality - Leduc, Joé G.; Boucher, Frédéric; Marques, Dominic L.; Brunelle, Eric (Frontiers in Sports and Active Living, 2024)
Purpose: The present study sought to understand the relationships between team identification, leader-member exchange (LMX) quality, and the basic psychological need satisfaction of collegiate athletes, as well as the moderating role of coach-athlete LMX quality. Methods: Self-reported data from 319 collegiate athletes were analyzed using SPSS version 29. The relationships between the study variables were tested by moderation analysis using PROCESS macro model 1. Results: Regression analyses showed team identification to be positively related to the satisfaction of the needs for competence and relatedness, while LMX quality was positively related to the satisfaction of the needs for competence and autonomy. Furthermore, moderation analyses showed that LMX quality positively moderated the relationship between team identification and the satisfaction of the needs for competence and relatedness.The results of this study highlight the important role that team identification and LMX quality play in the satisfaction of the basic psychological needs of collegiate athletes. The implications of these results for the optimal functioning of collegiate athletes are discussed.